Prevalence of obesity among U.S. population with substance dependence. (1st December 2020) - Hu, Lian; Oden, Neal; Tai, Betty; VanVeldhuisen, Paul
Highlights: Heroin-, marijuana-, nicotine-, and alcohol-dependent individuals were less likely to be obese than their non-dependent counterparts. Heroin-dependent individuals were least likely to be obese. Main findings in this report are consistent with our prior report based on substance abuse treatment clinical trials. Abstract: Aim: To investigate associations between substance dependence and obesity. Methods: Obesity (body mass index ≥ 30 kg/m 2 ) status and the status of dependence on heroin, stimulant, marijuana, nicotine and alcohol (past-month status for nicotine and past-year status for all others) were identified from the U.S. National Survey on Drug Use and Health (NSDUH, 2015–2017) datasets. SAS Surveylogistic regression was used to estimate adjusted odds ratio (AOR) for the association between each substance dependence and obesity, adjusting for potentially confounding effects of sociodemographic factors and health condition. Results: It was estimated that 10.6 % of noninstitutional U.S. residents aged 12 years or older were nicotine-dependent, 3.0 % alcohol-dependent, 1.0 % marijuana-dependent, 0.6 % stimulant-dependent, and 0.2 % heroin-dependent. Heroin-dependent individuals had 59 % lower odds of obesity relative to their non-dependent counterparts (AOR = 0.41; 95 % CI: 0.28−0.60; p < 0.0001). Lower odds of obesity were also noted for marijuana-dependent (AOR = 0.64; 95 % CI: 0.56−0.73; p < 0.0001), nicotine-dependent (AOR = 0.68; 95 % CI: 0.64−0.72; p < 0.0001) and alcohol-dependent (AOR = 0.77, 95 % CI: 0.69−0.84; p < 0.0001) individuals, but not statistically significant for stimulant-dependent individuals (AOR = 0.84; 95 % CI: 0.68−1.02; p = 0.0825). Conclusions: Heroin, marijuana, nicotine and alcohol dependence were associated with lower odds of obesity than their non-dependence counterparts. Main findings based on 2015–2017 NSDUH are consistent with findings from our prior report based on clinical trials data from National Institute on Drug Abuse Clinical Trials Network, and other epidemiological evidence in the literature. These findings can alert substance abuse treatment professionals to monitor weight change, especially among weight-concerned substance abusers.